Feed forward neural network based learning scheme for cognitive radio systems - Gatla, V; Venkatesan, M; Kulkarni, A.V (Proceedings of third International Conference on Computational Intelligence and Information Technology, 2013)
Intelligence is needed to keep up with the rapid evolution of wireless communications, especially in terms of managing and allocating the scarce, radio spectrum in the highly varying and disparate modern environments. Cognitive radio systems promise to handle this situation by utilizing intelligent software packages that enrich their transceiver with radio-awareness, adaptability and capability to learn. In such a process, learning mechanisms that are capable of exploiting measurements sensed from the environment, gathered experience and stored knowledge, are judged as rather beneficial for guiding decisions and actions. This paper introduces and evaluates a learning scheme that is based on artificial neural networks and can be used for predicting the capabilities (e.g. data rate) that can be achieved by a specific radio configuration. This can be used for judging the performance (e.g. throughput, data rate) that can be achieved by a specific radio configuration under certain environmental conditions in cognitive radio systems.